2020
DOI: 10.3389/fimmu.2020.570681
|View full text |Cite
|
Sign up to set email alerts
|

Immune Mechanisms in Cardiovascular Diseases Associated With Viral Infection

Abstract: Influenza virus infection causes 3-5 million cases of severe illness and 250,000-500,000 deaths worldwide annually. Although pneumonia is the most common complication associated with influenza, there are several reports demonstrating increased risk for cardiovascular diseases. Several clinical case reports, as well as both prospective and retrospective studies, have shown that influenza can trigger cardiovascular events including myocardial infarction (MI), myocarditis, ventricular arrhythmia, and heart failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 219 publications
(260 reference statements)
2
28
1
4
Order By: Relevance
“…Due to the pathophysiological processes involved in SARS-CoV-2 infection, HF is an important vulnerability during respiratory viral infections [ 9 , 10 ]. These pathways tend to HF decompensation and an increased risk of arrhythmia and ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the pathophysiological processes involved in SARS-CoV-2 infection, HF is an important vulnerability during respiratory viral infections [ 9 , 10 ]. These pathways tend to HF decompensation and an increased risk of arrhythmia and ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…These effects range from abnormal electrocardiogram findings such as tachycardia, 26 atrial fibrillation, 24 , 27 or even life threatening ventricular arrhythmias 25 and adverse cardiac events. 28 Taken in combination, these findings may explain why tachycardia can be a predictor of influenza infection. Of note, one study reported that during influenza infection, electrocardiogram confirmed tachycardia resolves by Day 2 of infection, 26 hence limiting the use of this marker to early presentations only.…”
Section: Discussionmentioning
confidence: 98%
“…Acute influenza‐associated cardiac events are especially prevalent in patients with pre‐existing cardiovascular disease and include heart attacks and failure [83]. Due to strong support for the role of systemic inflammation in cardiovascular disease following respiratory viral infection [84], a number of studies have modeled these effects within mice and other animal models absent direct infection of cardiac tissues.…”
Section: Cardiovascular Effects and Effectorsmentioning
confidence: 99%